Removing the burden of syntax: developing computational thinking and algorithmic skills of STEM students - Gulácsi, Ádám; Csernoch, Maria (Teaching Mathematics and Computer Science, 2026)
In higher education, solving programming exercises using a high-level programming language is a standard approach for developing computational thinking and algorithmic skills. However, this method has its limitations: learning the syntax of a high-level programming language puts an extra cognitive load on students, preventing them from focusing on problem-solving. Furthermore, computational thinking is not limited to programming: STEM students can benefit more from solving problems within their own discipline, in different environments. This practical article proposes a collection of unplugged, semi-unplugged and plugged-in alternatives that can be used to develop the computational thinking and algorithmic skills of students.Subject Classification: 97P99